Perlindungan Hak Jurnalis Terkait Ujaran Kebencian dalam Hukum Positif Indonesia - Maria Yeti Andrias; Farida Tuharea; Yulianus Payzon Aituru; Irsan Irsan; Apripari Apripari (Al-Mizan (e-Journal), 2023)
This study aims to analyze the protection of journalists' rights regarding hate speech in Law Number 19 of 2016 concerning Information and Transactions and the protection mechanisms regulated in Law Number 40 of 1999 concerning the Press. The research method used is the normative method with the Statute Approach approach and is processed using the legal hermeneutic method. The results of the study show that article 28, paragraph (3) regarding hate speech in the ITE Law is an article that has multiple interpretations and is prone to misuse. The ITE Law can also set aside the Press Law as a lex specialist in protecting journalists. Meanwhile, the Press Law has a mechanism for preserving the journalist profession, such as the right of reply, the right of correction, a Memorandum of Understanding between the Press Council and the Indonesian National Police, and dispute resolution through the Press Council. This research reveals that the ITE Law and the Press Law differ in protecting journalists' rights regarding hate speech.